A Case Study of Blue Ocean Strategy in Indonesian Sharia Bank Ambarukmo Yogyakarta - Rifki Husen Alhasni (ABHATS: Jurnal Islam Ulil Albab, 2021)
With intense competition in the field of in this banking sector, the bank must develop an appropriate strategy in order to survive for outperform competitors. Destination study this create a innovative products and to identify and analyze the position of Islamic banking in determining strategy the right way to attract potential customers. Method from study this is use qualitative with field research assistance using survey to Bank Syariah Indonesia customer KC Ambarukmo. Collected data used for ERRC Grid or framework 4 step work for produce Blue Ocean Strategy. After analyze survey results using ERRC Grid generated a product innovative called _ MASPRO is aimed at to less students _ capable and accomplished as well as productive. Product innovative this uses Blue Ocean Strategy. Based on results study could concluded that product MASPRO could make a breakthrough for outperform competitors. Supported with enthusiasm customer as respondent to product innovative.